Burma '44 the battle that turned World War II in the East - Holland, James 1970- (Atlantic Monthly Press, 2024)
"Celebrated historian of World War II James Holland chronicles the astonishing Allied victory at the Battle of the Admin Box in Burma (now Myanmar), a turning point of the war in the Far East. In February 1944, in one of the most astonishing battles of World War II, a ragtag collection of British clerks, drivers, doctors, muleteers, and other base troops, stiffened by a few dogged Yorkshiremen and a handful of tank crews, managed to defeat a much larger and sophisticated contingent of some of the finest infantry in the Japanese army on their march towards India. What became known as the Battle of the Admin Box, fought amongst the paddy fields and jungle of Northern Arakan over a fifteen-day period, turned the battle for Burma. Not only was it the first decisive victory for British troops against the Japanese, more significantly, it demonstrated how the Japanese could be defeated. Lessons learned in this tiny and otherwise insignificant corner of the Far East, set up the campaign in Burma that would follow, as General William Slim's Fourteenth Army finally turned defeat into victory. In Burma '44, acclaimed World War II historian James Holland offers a dramatic tale of victory against incredible odds. As momentous as the Battle of the Bulge ten months later, the Admin Box was a triumph of human grit and heroism and remains one of the most significant yet undervalued conflicts of the entire war. In Holland's hands, it is finally given its proper place in the history of the war."
First published in 2016 in Great Britain by Bantam Press, an imprint of Transworld Publishers
Keywords: Geschichte 1944; Schlacht; Zweiter Weltkrieg; Arakan; World War, 1939-1945 / Campaigns / Burma; World War, 1939-1945 / Great Britain; World War, 1939-1945 / Japan